PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Nugraha, Muhamad Kemal; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
firm value. This research has been carried out on 21 samples manufacturing companies which are listed inIndonesia Stock Exchange in 2010-2015 periods. The analysis has been conducted by using multiple linearregressions analysis, F test, and t test.Based on the result of this research, it has been found that financialperformance has significant and positive influence to the firm value. The existence of significant influence iscaused by the financial performance shows good prospect, so these stocks will be attractive to the investorstherefore the firm value will increase. Firm size does not have any significant influence to the firm value becausefirm size is in line with its business risk, when the firm size is getting large; the business risk is getting large aswell. The investment decision has significant and positive influence to the firm value because high PER will givea description that the company is health and has a well growth, so that the firm value will increase in front of theinvestors.Investors and potential investors are suggested to pay attention to financial statement as theconsideration in making correct and profitable investment decision.Keywords : Financial performance, firm size, investment decision, firm value.